Thermal power fluctuations in waste heat to power systems : an overview on the challenges and current solutions - Jiménez-Arreola, Manuel (2020)
Waste Heat to Power (WHP) represents an enormous opportunity to increase energy efficiency of various industry sectors and to reduce emissions and waste of primary sources. However, thermal power fluctuations are often present in waste heat from industrial processes and transport sectors. These fluctuations negatively affect the operation and economic feasibility of heat recovery power systems such as Steam and/or Organic Rankine Cycle. Due to the lack of literature in this topic, the current paper presents an overview of thermal power fluctuations in waste heat, the related issues affecting the recovery power systems and the available solutions for the problem. Different measures to compensate the fluctuations of different waste heat sources are reviewed, including stream control and intermediary storage units such as the standard sensible heat thermal oil loops systems and more sophisticated latent heat storage technologies based on phase-change materials. The economic considerations required for the WHP systems operating under fluctuating sources are also discussed.